Eating problems in adolescents with Type 1 diabetes: a systematic review with meta‐analysis. Issue 2 (21st January 2013) - Young, V.; Eiser, C.; Johnson, B.; Brierley, S.; Epton, T.; Elliott, J.; Heller, S.
<x xml:space="preserve">Abstract</x> Diabet. Med. 30, 189–198 (2013) Abstract Aims We report a systematic review to determine (1) prevalence of eating problems compared with peers and (2) the association between eating problems and glycaemic control in young adults with Type 1 diabetes. Method We conducted a systematic literature search via electronic databases and meta‐analysis. Cohen's d (the mean difference score between Type 1 diabetes and comparison groups) was calculated for 13 studies that met inclusion criteria. Results Eating problems [both disordered eating behaviour (39.3 and 32.5%; d = 0.52, 95% CI 0.10–0.94) and eating disorders (7.0 and 2.8%; d = 0.46, 95% CI 0.10–0.81)] were more common in adolescents with Type 1 diabetes compared with peers and both were associated with poorer glycaemic control (d = 0.40, 95% CI 0.17–0.64). In restricted analyses involving measures adapted for diabetes, associations between eating problems and poorer glycaemic control remained (d = 0.54, 95% CI 0.32–0.76). Disordered eating behaviour (51.8 and 48.1%; d = 0.06, 95% CI −0.05 to 0.21) and eating disorders (6.4 and 3.0%; d = 0.43, 95% CI −0.06 to 0.91) were more common in adolescents with Type 1 diabetes compared with peers, but differences were non‐significant. Conclusions Eating problems are common among this age group. Future work in populations with Type 1 diabetes should develop sensitive measures of eating problems and interventions, and establish predictors of eating problems. Screening in clinics is recommended.